2020
DOI: 10.3390/ijerph18010121
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change, Pesticides and Health: Considering the Risks and Opportunities of Adaptation for Zimbabwean Smallholder Cotton Growers

Abstract: There is potential for increased pesticide-related adverse health outcomes in the agricultural sector linked to adaptive increases in pesticide use necessitated, in part, by climate change-related increases in pest populations. To understand the role of adaptation practices in pesticide use and health risks, this study assessed Zimbabwean smallholder cotton farmers’ adaptive responses linked to their climate change perceptions. In depth interviews were conducted with 50 farmers who had been growing cotton for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 62 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…In contrast, a previous study conducted in Zimbabwe over two years suggested a lower figure of 32% due to intentional poisoning (Tagwireyi et al 2002). The difference between these two studies can be attributed to the increased use of pesticides in Zimbabwe during the last two decades (Zinyemba et al 2021). Several studies in Low to LMIC countries Iran, Sri Lanka and India have reported that the intentional use of pesticides for poisoning is a significant challenge associated with pesticide use (Jesslin et al 2010;Razwiedani and Rautenbach 2017;Noghrehchi et al 2022;Chan et al 2023).…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, a previous study conducted in Zimbabwe over two years suggested a lower figure of 32% due to intentional poisoning (Tagwireyi et al 2002). The difference between these two studies can be attributed to the increased use of pesticides in Zimbabwe during the last two decades (Zinyemba et al 2021). Several studies in Low to LMIC countries Iran, Sri Lanka and India have reported that the intentional use of pesticides for poisoning is a significant challenge associated with pesticide use (Jesslin et al 2010;Razwiedani and Rautenbach 2017;Noghrehchi et al 2022;Chan et al 2023).…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, a timely approach to optimize the agricultural input and production combination can help peasant households to mitigate the negative effects of risks and to adopt adaptive measures. Local governments and related departments should focus on these research findings to develop reasonable agricultural risk management policies [ 65 ]. The government can increase the early warning and forecasting of weather and disaster information.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial for organisation to mitigate bias in all aspects of HR function. Especially, in Global South countries many processes in HR like recruitment, training and performance appraisal done based on nepotism or favouritism (e.g., Zinyemba, 2014;Subat et al, 2020). In respect to that, AI-based system will reduce the possibilities of this kind of bias (Nawaz, 2019;Rathi, 2018;Upadhyay & Khandelwal, 2018;Bora & Borah, 2020) by ignoring some irrelevant information (e.g., gender, marital status, weight, and race) or insignificant perception (e.g.…”
Section: Mitigating Human Biasesmentioning
confidence: 99%